Body Composition Characteristics and Anthropometric Measurements of Older Mongolian Adults - Byambasukh, Oyuntugs; Buukuu, Gerel; Chinbat, Odgerel (Central Asian Journal of Medical Sciences, 2023)
Objectives: The purpose of our study is to examine characteristics of body composition and anthropometric measurements in older Mongolian adults. Methods: This cross-sectional study included 268 individuals aged 45 years and older who visited national hospitals over a period of one month. Body weight, BMI, waist circumference (WC) and other body circumferences, and body composition (body fat percentages, fat-free mass index, skeletal mass index) were measured and the Short Physical Performance Battery (SPPB) score was used to test the physical performance. Results: The sample was composed of 73.7% women and 26.3% men, and the mean age was 58.1±8.9. All measurements were relatively higher than the normal range in older Mongolian adults. Obesity in women was relatively higher than men. 77.1% of all participants were obese according to BMI, 92.5% were obese according to body fat percentage, and 96.2% were centrally obese according to WC. Among people aged 45-64 years, prevalence of obesity increased and then decreased in ages 65-74 years. Age was significantly correlated with WC and the SPPB score was indirectly correlated with age (p<0.05). Conclusion: Obesity in older Mongolian adults is comparatively higher for women and tends to increase with age.>